Principal Leadership in the 'Merdeka Belajar' Era: Fostering Synergy for Educational Transformation - Sovia Mas Ayu; Asmara Dewi (Al-Qalam Institue, 2023)
The research will explore how school principals work together with various stakeholders, show work intensity, and show innovative learning attitudes to improve the quality of education. The purpose of this study is to describe the leadership of the principal of dRais School Kindergarten Bandar Lampung in creating synergy in the era of 'Merdeka Belajar' using the method popularized by Miles and Huberman. The research data was obtained from participants, namely the principal and teachers. Data collection was carried out through interviews, observation, and documentation. Data analysis was conducted in three stages: data reduction, data display, and conclusion drawing or verification. The results showed that the leadership of the principal of dRais School Kindergarten in creating synergy is achieved in three ways: by collaborating, showing work intensity, and always trying to show an innovative learning attitude.